Type 0 Spinal Muscular Atrophy in rare association with congenital contracture and generalized osteopenia: A Case Report - Singh, Aditi; Dalal, Poonam; Singh, Jasbir; Tripathi, Pooja (Iranian Journal of Child Neurology, 2018)
Abstract Spinal muscular atrophy (SMAs) is a group of rare autosomal recessive diseases in which there is degeneration of alpha motor neurons in the spinal cord leading to progressive distal motor weakness. Here we report a case of type 0 SMA in newborn with generalized osteopenia and bony deformity in form of unilateral club foot. It may be emphasized that diagnosis of SMA should be kept in mind as a differential in cases of unexplained severe generalized hypotonia and severe respiratory compromise immediately after birth.